Effect of Extract Omega-3 Fatty Acids Consumption from Mackerel as Adjuvant of Antidepressant Fluoxetine (Rastrelliger kanagurta) on Decreasing Cortisol Hormone Levels - Aisyah Izzatinisa; Novita Angkirani; Zabrina Zerlinda; Jessica William; Azizah Hanun Yasmin; Ziske Maritska (Sriwijaya Journal of Medicine, 2022)
Depression, one of the common mental disorders; generally identified by feelings of sadness or disappointment when experiencing a change, loss, or failure and becomes pathological when unable to adapt. According to WHO, Indonesians have a suicide ratio of 3,7 per 100.000 population. People with depression have some dysfunction in the hypothalamic-pituitary-adrenal (HPA) axis, which takes a part in the organism's reaction to depression. As a hormonal response to stress signals, thus the cortisol hormone will be released. The cortisol hormone mainly modulates emotions, especially fear and anxiety. Hence, patients with depression tend to have higher cortisol hormone levels. The most commonly used psychopharmacological medication is antidepressants. However, only about 40-60 out of 100 individuals are helped by taking antidepressants. Thereupon, as support for antidepressants, an adjuvant, i.e., omega-3 fatty acids in mackerel (Rastrelliger kanagurta) is needed. Therefore, the author uses Google Scholar, WHO, PubMed, and HealthLine as references for this literature review. After reviewing the literature, omega-3 fatty acids in mackerel can act as an adjuvant to antidepressants in lowering cortisol hormone levels. The dosage of omega-3 fatty acids needs to be analyzed to optimize the potential of adjuvant therapy for fluoxetine.